Balsem Ekstrak Jahe Merah sebagai Alternatif Pereda Dysmenorrhea: Studi Quasi-Eksperimental dengan Kelompok Kontrol - Handayani, Rika; Fachriani, Ayu; Haji Saeni, Rahmat; Yulianti, Nila Trisna (Jurnal Kesehatan Manarang, 2025)
Dysmenorrhea is pain in the lower abdomen to the pelvic area during menstruation, which can interfere with the daily activities of adolescent girls. This study aims to evaluate the effectiveness of red ginger (Zingiber officinale var. rubrum) extract balm in reducing menstrual pain levels among adolescent girls at SMPN 8 Makassar. The research design used is a Quasi-Experimental Pretest-Posttest Control Group Design, where measurements were conducted before and after the intervention in both the intervention and control groups. A total of 66 ninth-grade students were selected using a purposive sampling technique and were divided into two groups: the intervention group and the control group. Data were analyzed using non-parametric statistical methods, namely the Wilcoxon Signed Rank Test and Mann-Whitney U Test. The Wilcoxon test results showed a significant reduction in pain levels in the intervention group with a Z value of -4.799 and a p-value of 0.000. The Mann-Whitney U test results indicated a significant difference between the intervention and control groups (p = 0.000), with the intervention group having a lower mean rank (24.52) compared to the control group (42.48). These findings suggest that the application of red ginger extract balm is effective in reducing menstrual pain intensity. Thus, using red ginger-based balm can be considered a practical and effective non-pharmacological alternative therapy for managing dysmenorrhea. Further research is needed to explore the optimal duration of use and effectiveness across a broader age group.